Design of Electrostatic Comb Actuators based on Finite Element Method - Mon, Thet Thet; Z., Ghazalli; Asnul Hadi, Ahmad; Mohd Fazli, Ismail; Khairul Fikri, Muhammad (2010)
Electrostatic comb actuators are commonly used to provide displacement-invariant force in micro electro-mechanical system (MEMS). Major application can be found in resonator, inertial sensor, accelerometer, and gyroscope. The size of the comb may be a few microns to millimeters. Principally, the electrostatic force is produced in the comb structure due to potential difference between the electrodes, which is used to actuate the system attached to it. The higher forces are very often desirable for high sensitivity and performance. However to meet this demand, micro-scaled structures are very often fabricated on trial-error basis because of lack of well established fabrication method. In this situation, designing on a computer prior to the actual fabrication would be very helpful. Moreover, in a virtual device, parameters can be changed much more quickly than trial-and-error fabrication reducing the time to market and also the cost to develop a commercial device considerably. The aim of this paper is to present finite element modeling and analysis to design comb structure, and its limitation for realistic design. Design objective is to achieve higher actuation force. Since a computational model for design analysis at micro-scale based on FEM is never obsolete, this work will be useful for those who seek designing MEMS components in FEM as well as facilitate the MEMS industry to economically obtain feasible design parameters for micro-scaled devices.